Dynamics Simulation of the Tooth Root Crack Fault of Gear Transmission System - Ning Shaohui; Han Zhennan; Li Yuexian; Wu Xuefeng (Jixie chuandong)
Taking the coupling dynamics modeling of spur gear pairs as the research object,considering the time- varying meshing stiffness of teeth and the friction between teeth,two models of different mesh stiffness of fault and intact gear are established. The two models time- varying meshing stiffness are calculated by the finite element method,the results show that the crack will reduce the meshing stiffness of gear,the greater the crack,the smaller the meshing stiffness. By using the Matlab,the dynamics differential equations of the model are solved,the angular velocity and angular acceleration simulation curve of the two kinds of fault and intact gear are got,the result is that the gear turning crack,angular velocity and angular acceleration of the driven produced obvious fluctuations,the calculation results are consistent with theoretical analysis.